Students’ Interest in Learning Mathematics through Aquascape Project-Based Learning at Vocational High School - Sholihat, M. Nuur'aini; Dwiyanti, Widya (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
The low interest in learning mathematics for vocational students is still a problem in the world of education. The orientation of vocational education emphasizes the application of knowledge in practical and real contexts. Therefore, the relevance of each subject to the competence of students’ expertise is important. This study aims to determine the interest in learning mathematics of grade X APAT students at SMK PPN Tanjungsari in aquascape project-based learning. The research method used is qualitative descriptive. Data was collected through observation sheets, student interest questionnaires, interviews, and documentation. Data analysis was conducted using the average percentage of student learning interest. The results showed that students' interest in learning mathematics in aquascape project-based learning reached a high level, which was 67.32%. These results can make a positive contribution to learning practices and provide a foundation for further research in the fields of mathematics, science, and Landscaping and Gardening. The implications of these results could be the basis for the development of more effective and interest-oriented learning strategies for subsequent students.